STUDI KELAYAKAN PEMBANGKIT LISTRIK TENAGA SURYA UNTUK PENERANGAN DI LOKASI WISATA PANTAI GEMAH TULUNGAGUNG JAWA TIMUR - Udianto, Pondi; Asrori, Asrori; Yudianto, Eko (INFO-TEKNIK, 2020)
The condition of electric energy at Gemah beach on the south coast of Tulungagung has not been fully supplied by PLN, so it is necessary to take advantage of renewable energy. This study aims to calculate the need for electrical energy at Gemah beach and calculate the number of solar panels and the required generating capacity. From the calculation results obtained: Total load energy per day 17392 Wh, Total load Ah requirement per day = 362 Ah, and need battery with capacity = 1358 Ah, capacity of selected battery in Amp-hour is 800 Ah, batteries in parallel is 2, Number of batteries in series = 24, Total number of batteries = 48, capacity of total battery is 1600 Ah, Total kilowatt-hour capacity of battery = 76.8 kWh. Meanwhile, for the purposes of generation required: The number of solar modules to meet the load requirements = 28 modules. Generating capacity = 5.6 kWp, rounded off to 6 kWp